P.065 Alzheimer's disease (AD) and dementias in Canada: First national surveillance data from the Canadian Chronic Disease Surveillance System (CCDSS). (2nd June 2017) - Pelletier, C; Robitaille, C; Gabora-Roth, N; Toews, J
Abstract : Background: With a growing and aging population, the number of individuals with AD and dementias and their associated costs are expected to increase in Canada. Up to now, no national mechanism was in place to monitor the epidemiological burden of AD and dementias. This presentation will showcase the first CCDSS data available on these conditions.Methods: Through the CCDSS, a Federal/Provincial/Territorial partnership, health administrative databases are linked to collect data on chronic conditions. Using selected ICD-9(CM)/ICD-10 codes for AD and dementias, the validated case definition implemented to identify relevant cases aged 65+ is: 1+ hospitalizations; or 3+ physician claims within 2 years, with a 30-day-gap between each claim; or 1+ anti-dementia drug prescriptions. Prevalence and incidence rates will be presented by 5-year age group, sex, province/territory, and fiscal year.Results: Overall, incidence and prevalence rates were higher in women. The prevalence rate approximately doubled between 5-year age groups and sex differences tended to widen with age. While aged-standardised data show increasing prevalence rates over time, incidence rates fluctuated but suggest a decline since 2009/10.Conclusions: CCDSS data can be used to monitor the burden of AD and dementias in Canada. This information is important for the assessment of prevention actions and the planning of health care resources.